Nilotinib effects on safety, tolerability, and biomarkers in Alzheimer's disease: A phase 2, double‐blind, randomized, placebo‐controlled trial: Human/Human trials: Anti‐amyloid. (7th December 2020) - Turner, Raymond Scott; Hebron, Michaeline; Lawler, Abigail; Mundel, Elizabeth; Yusuf, Nadia; Starr, Nathan; Pagan, Fernando; Torres‐Yaghi, Yasar; Shi, Wangke; Mulki, Sanjana; Ferrante, Dalila; Matar, Sara; et al.
Abstract: Background: The goal is to assess the safety, tolerability, and pharmacokinetics of nilotinib, and measure biomarkers in participants with mild to moderate dementia due to Alzheimer's disease. We hypothesized that nilotinib is safe and detectable in cerebrospinal fluid. Nilotinib may alter disease biomarkers and potentially slow clinical decline. Method: This is a single‐center, phase 2, randomized, double‐blind, placebo‐controlled study. Of 117 individuals approached, 13 declined, 51 were excluded, 51 were screened, and 37 were randomized 1:1 to placebo or nilotinib groups. The Alzheimer's disease diagnosis was supported by cerebrospinal fluid or amyloid positron emission tomography biomarkers. Nilotinib 150 mg vs matching placebo was taken orally once daily for 26 weeks followed by nilotinib 300 mg vs placebo for another 26 weeks. Result: Of the 37 individuals enrolled, 27 were women (73%), and the mean (SD) age was 70.7 (6.48) years. Nilotinib was safe and well‐tolerated, although more adverse events, particularly mood swings, were noted at the 300 mg dose (70.6%) vs placebo (0%) groups (p<.01). In the nilotinib group, amyloid burden was reduced in the temporal (‐0.08, 90% CI, ‐0.21 to ‐0.01, p=.04) and frontal lobes (‐0.19, 90% CI, ‐2.29 to ‐0.08, p<.001) compared to the placebo group. Cerebrospinal fluid Aβ40 was reduced at 6 months (566ng/ml, 90% CI, 135 to 1018, p=.02) and Aβ42 was reduced at 12 months (73.9 ng/ml, 90% CI, 14.3 to 137.9, p=.02) in the nilotinib group compared to the placebo. Hippocampal volume loss was attenuated (‐27%) at 12 months and phospho‐tau181 was reduced at 6 months (‐31.6%) and 12 months (‐39.6%) in the nilotinib group. Conclusion: Nilotinib is safe and well‐tolerated, and achieves pharmacologically relevant brain concentrations. Biomarkers of Alzheimer's disease were altered in response to nilotinib treatment. These data support a larger, multi‐center, phase 3 study to determine the safety and efficacy of nilotinib in Alzheimer's disease. ClinicalTrials.gov NCT02947893.